A Bibliometric Analysis of Climate Investing - Joshi, Girish; Dash, Ranjan (International Journal of Energy Economics and Policy, 2023)
This research article seeks to provide a comprehensive review of climate investing and anticipated future developments by using bibliometric study. Climate investing is a well-researched subject of study, and the massive increase in publications in recent years indicate the breadth and depth of the topic. Affiliation statistics show that the majority of research is centered in the USA, Australia and the UK, offering up new possibilities for climate investing research in developing countries. The authors examined 1091 articles related to climate investing from the Scopus database since 1971, using the bibliometric review technique to provide numerous viewpoints from previous climate investing studies associated with carbon offsetting, green bonds, impact investing, sustainable stock indices, climate-themed funds, ESG screening, divestment from fossil fuels, climate-aligned funds, and climate-smart agribusiness and suggests future study directions. This research may be helpful to policy makers, particularly those from developing nations, in understanding the challenges of climate investing.